Cerebral Amyloid Angiopathy Presenting as Massive Subarachnoid Haemorrhage: A Case Study and Review of Literature - Saito, Satoshi; Ikeda, Yoshihiko; Ando, Daisuke; Carare, Roxana Octavia; Ishibashi-Ueda, Hatsue; Ihara, Masafumi (Frontiers in Aging Neuroscience, 2020)
Cerebral amyloid angiopathy (CAA) is characterized by the progressive accumulation of β-amyloid (Aβ) in the walls of cerebral capillaries and arteries representing a major cause of haemorrhagic stroke including lobar intracerebral haemorrhage (ICH) and convexity subarachnoid haemorrhage (SAH). Haemorrhaging from CAA predominantly involves smaller arteries rather than arterial aneurysm. Restricted bleeding into the subarachnoid space in CAA results in asymptomatic or mild symptomatic SAH. Herein, we present an autopsied case of massive SAH related to CAA. An eighty-nine-year-old male with a history of mild Alzheimer’s disease and advanced pancreatic cancer with liver metastasis developed sudden onset of coma. Head CT illustrated ICH located in the right frontal lobe and right insula, as well as SAH bilaterally spreading from the basal cistern to the Sylvian fissure, with hydrocephalus and brain herniation. He died about 24 hours after onset and the post-mortem examination showed no evidence of arterial aneurysm. The substantial accumulation of Aβ in the vessels around the haemorrhagic lesions led to the diagnosis of ICH related to CAA and secondary SAH, which may have been aggravated by old age and malignancy. This case suggests CAA can cause severe SAH resembling aneurysmal origin and thus may be overlooked when complicated by atypical cerebral haemorrhage.